Integrated Communication As a Instrument For Building The Image of Hospital - Nuriyati Samaatan; Dian Metha Ariyanti; Robingah Robingah; Jun Firmansyah; Hendrik K. H. (Siber Journal of Advanced Multidisciplinary, 2025)
This study aims to determine the integrated communication model as an instrument in building the image of Hospital. The method used in this study is a descriptive qualitative method with a Social Image theory and Berlo Communication Model approach. Data was collected through in-depth interviews with Hospital's Public Relations department and observation of communication activities carried out both internally and externally. The results of the study show that EMHAKA Bekasi Hospital's Public Relations department implements various communication strategies, including the use of social media, relationships with the mass media, and direct communication with the community through social events and health seminars. This is done to increase public understanding of the services provided by the hospital and create a positive impression of the quality of services offered. With effective communication strategies, Hospital has succeeded in building a positive image in the community, which has an impact on patient trust and loyalty. This study provides an overview of the important role of public relations communication in shaping the image of a health institution in the eyes of the public.